Reassessing the clinical spectrum associated with hereditary leiomyomatosis and renal cell carcinoma syndrome in French FH mutation carriers. Issue 6 (2nd May 2017) - Muller, M.; Ferlicot, S.; Guillaud‐Bataille, M.; Le Teuff, G.; Genestie, C.; Deveaux, S.; Slama, A.; Poulalhon, N.; Escudier, B.; Albiges, L.; Soufir, N.; Avril, M.‐F.; et al.
Abstract : We addressed uncertainties regarding hereditary leiomyomatosis and renal cell carcinoma (HLRCC) by exploring all French cases, representing the largest series to date. Fumarate hydratase (FH) germline testing was performed with Sanger sequencing and qPCR/MLPA. Enzyme activity was measured when necessary. We carried out whenever possible a pathology review of RCC and S‐(2‐succino)‐cysteine (2SC)/fumarate hydratase immunohistochemistry. We estimated survival using non‐parametric Kaplan‐Meier. There were 182 cases from 114 families. Thirty‐seven RCC were diagnosed in 34 carriers (19%) at a median age of 40. Among the 23 RCC with pathology review, 13 were papillary type 2. There were 4 papillary RCC of unspecified type, 3 unclassified, 2 tubulocystic, and 1 collecting duct (CD) RCC, all 2SC+ and most (8/10) FH−. Of the remaining 14, papillary type 2, papillary unspecified, CD, and clear cell histologies were reported. The vast majority of RCC (82%) were metastatic at diagnosis or rapidly became metastatic. Median survival for metastatic disease was 18 months (95%CI: 11‐29). 133 cases (73%) had a history of cutaneous leiomyomas, 3 developed skin leiomyosarcoma. Uterine leiomyomas were frequent in women (77%), but no sarcomas were observed. Only 2 cases had pheochromocytomas/paraganglioma. Conclusion: Our findings have direct implications regarding the identification and management of HLRCC patients. Abstract :